ARTISTIC INTERPRETATION OF THE CONTENT OF HADITHS IN THE RUBAIYATS OF ALISHER NAVOI (International journal of artificial intelligence, 2026)
This article examines the rubaiyats included in Alisher Navoi’s Arba'in, focusing on the artistic interpretation of hadith content and its poetic realization. The study analyzes how Navoi transforms the moral and theological essence of hadiths into independent artistic works, achieving a synthesis of religious meaning and poetic aesthetics.